Precipitation and growth of barite within hydrothermal vent deposits from the Endeavour Segment, Juan de Fuca Ridge. (15th January 2016) - Jamieson, John William; Hannington, Mark D.; Tivey, Margaret K.; Hansteen, Thor; Williamson, Nicole M.-B.; Stewart, Margaret; Fietzke, Jan; Butterfield, David; Frische, Matthias; Allen, Leigh; Cousens, Brian; Langer, Julia
Abstract: Hydrothermal vent deposits form on the seafloor as a result of cooling and mixing of hot hydrothermal fluids with cold seawater. Amongst the major sulfide and sulfate minerals that are preserved at vent sites, barite (BaSO4 ) is unique because it requires the direct mixing of Ba-rich hydrothermal fluid with sulfate-rich seawater in order for precipitation to occur. Because of its extremely low solubility, barite crystals preserve geochemical fingerprints associated with conditions of formation. Here, we present data from petrographic and geochemical analyses of hydrothermal barite from the Endeavour Segment of the Juan de Fuca Ridge, northeast Pacific Ocean, in order to determine the physical and chemical conditions under which barite precipitates within seafloor hydrothermal vent systems. Petrographic analyses of 22 barite-rich samples show a range of barite crystal morphologies: dendritic and acicular barite forms near the exterior vent walls, whereas larger bladed and tabular crystals occur within the interior of chimneys. A two component mixing model based on Sr concentrations and 87 Sr/ 86 Sr of both seawater and hydrothermal fluid, combined with 87 Sr/ 86 Sr data from whole rock and laser-ablation ICP-MS analyses of barite crystals indicate that barite precipitates from mixtures containing as low as 17% and as high as 88% hydrothermal fluid component, relative to seawater. Geochemical modelling of the relationship between aqueous species concentrations and degree of fluid mixing indicates that Ba 2+ availability is the dominant control on mineral saturation. Observations combined with model results support that dendritic barite forms from fluids of less than 40% hydrothermal component and with a saturation index greater than ∼0.6, whereas more euhedral crystals form at lower levels of supersaturation associated with greater contributions of hydrothermal fluid. Fluid inclusions within barite indicate formation temperatures of between ∼120 °C and 240 °C during barite crystallization. The comparison of fluid inclusion formation temperatures to modelled mixing temperatures indicates that conductive cooling of the vent fluid accounts for 60–120 °C reduction in fluid temperature. Strontium zonation within individual barite crystals records fluctuations in the amount of conductive cooling within chimney walls that may result from cyclical oscillations in hydrothermal fluid flux. Barite chemistry and morphology can be used as a reliable indicator for past conditions of mineralization within both extinct seafloor hydrothermal deposits and ancient land-based volcanogenic massive sulfide deposits.